2019
DOI: 10.3390/met9111189
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Microstructure and Mechanical Properties of Ti-6Al-4V/Al-1060 Explosive Welding

Abstract: The aim of this paper is to study the microstructure and mechanical properties of the Ti6Al4V/Al-1060 plate by explosive welding before and after heat treatment. The welded interface is smooth and straight without any jet trapping. The disturbances near the interface, circular and random pores of Al-1060, and beta phase grains of Ti6Al4V have been observed by Scanning electron microscopy (SEM). Heat treatment reduces pores significantly and generates a titanium-island-like morphology. Energy dispersive spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…However, significant differences were found for the upper limit. In turn, a coupled experimental/numerical work focused on studying the microstructure and the mechanical properties of titanium/aluminium explosion welds before and after being submitted to heat treatment was developed by Mahmood et al [2]. According to the authors, aluminium-titanium IMCs were formed at the weld interface, but these phases did not affect the weld strength.…”
Section: Contributionsmentioning
confidence: 99%
“…However, significant differences were found for the upper limit. In turn, a coupled experimental/numerical work focused on studying the microstructure and the mechanical properties of titanium/aluminium explosion welds before and after being submitted to heat treatment was developed by Mahmood et al [2]. According to the authors, aluminium-titanium IMCs were formed at the weld interface, but these phases did not affect the weld strength.…”
Section: Contributionsmentioning
confidence: 99%
“…Also, the author conducted bending and tensile-shear tests and showed that no fracture or separation happened in the bonding interface of the layers which illustrates that the explosive welding process is an appropriate way to bond the aluminum and copper layers. Mahmood et al 27 investigated the mechanical properties and microstructure of the aluminum/titanium explosively welded bimetallic sheet before and after the heat treatment. They found out that the pores at the interface of the layers are less in the specimen after heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of recent studies devoted to numerical simulation of high-velocity impact welding consider only few collision regimes providing only a limited understanding of the bonding phenomena [16][17][18]. Besides, most of the currently existing SPH studies on high-velocity impact welding simply state the fact of good agreement between the simulation results and experimentally observed interface.…”
Section: Introductionmentioning
confidence: 99%